(C5H6N4O)(C5H5N4O)3(C5H4N4O)[Bi2Cl11]Cl2 as a simple and efficient catalyst in Biginelli reaction. (4th October 2016) - Zhang, Xiang; Gu, Xiaoyu; Gao, Yuhua; Nie, Shipeng; Lu, Hongfei
Abstract : A highly efficient and facile procedure for the one‐pot three‐component synthesis of 3, 4‐dihydropyrimidin‐2‐(1 H )ones/thiones from the one‐pot condensation of aldehyde, β‐dicarbonyl compound and urea/thiourea was developed. The methodology is applicable to a wide range of substrates with high yield in the presence of (C5 H6 N4 O)(C5 H5 N4 O)3 (C5 H4 N4 O)[Bi2 Cl11 ]Cl2 . The complex is an air‐stable, environmentally friendly and recoverable catalyst and can efficiently catalyze the Biginelli reaction. The catalyst has high catalytic efficiency with low catalyst loading, and can be recycled ten times with only a small loss of activity. Abstract : An efficient and facile procedure for the one‐pot three‐component synthesis of 3, 4‐dihydropyrimidin‐2‐(1 H )ones/thiones was developed. The methodology is applicable to a wide range of substrates giving products in high yield in the presence of (C5 H6 N4 O)(C5 H5 N4 O)3 (C5 H4 N4 O)[Bi2 Cl11 ]Cl2 . The complex is an air‐stable, environmentally friendly, recoverable catalyst and can efficiently catalyze the Biginelli reaction. The catalyst has high efficiency with low loading, and could be recycled ten times with only a small loss of activity.